2020
DOI: 10.1111/jcpt.13247
|View full text |Cite
|
Sign up to set email alerts
|

Different effects of metformin on hypothalamic‐pituitary‐thyroid axis activity in levothyroxine‐treated and levothyroxine‐naïve women with non‐autoimmune hypothyroidism

Abstract: What is known and objective Metformin was found to reduce thyrotrophin levels in subjects with hypothyroidism. This case‐control study was aimed at comparing metformin action on hypothalamic‐pituitary‐thyroid axis activity between levothyroxine‐treated and levothyroxine‐naïve women with non‐autoimmune thyroid hypofunction. Methods The study included two groups of thyroid antibody‐negative women with thyrotrophin levels in the range between 4.5 and 10 mIU/L and untreated prediabetes, matched for age, body mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
2
0
1
Order By: Relevance
“…Interestingly, the obtained results are in line with the previous findings by Krysiak et al 21 and Casteràs et al 22 The first group of authors observed that levothyroxine/metformin combination therapy was superior to metformin alone in reducing thyrotropin levels in women with non-autoimmune subclinical thyroiditis, whilst the second one that levothyroxine requirements in thyroidectomized diabetic patients on metformin treatment were lower if individuals received metformin.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, the obtained results are in line with the previous findings by Krysiak et al 21 and Casteràs et al 22 The first group of authors observed that levothyroxine/metformin combination therapy was superior to metformin alone in reducing thyrotropin levels in women with non-autoimmune subclinical thyroiditis, whilst the second one that levothyroxine requirements in thyroidectomized diabetic patients on metformin treatment were lower if individuals received metformin.…”
Section: Discussionsupporting
confidence: 90%
“…Because metformin exerted its maximal effect on hypothalamic–pituitary–thyroid axis activity after 6 months of treatment, 20 the more potent effect of levothyroxine/metformin than levothyroxine/myo‐inositol combination therapy cannot be explained by the fact that the strength of metformin action increased with time. Interestingly, the obtained results are in line with the previous findings by Krysiak et al 21 and Casteràs et al 22 The first group of authors observed that levothyroxine/metformin combination therapy was superior to metformin alone in reducing thyrotropin levels in women with non‐autoimmune subclinical thyroiditis, whilst the second one that levothyroxine requirements in thyroidectomized diabetic patients on metformin treatment were lower if individuals received metformin.…”
Section: Discussionsupporting
confidence: 90%
“…From a theoretical point of view, a stronger impact of levothyroxine in subjects already treated with metformin can be attributed to interactions between metformin and levothyroxine and/or to the effect of metformin. In a recent study, the impact of high‐dose metformin treatment on thyrotropin levels was more pronounced in women simultaneously treated with levothyroxine than in women not receiving this hormone 21 . Although this finding suggests a synergistic action of metformin and levothyroxine, the present study contradicts this explanation.…”
Section: Discussioncontrasting
confidence: 87%